Reviewed Study on Postcolonialism and Hybridity in Amitav Ghosh's Novels: Exploring the Impact of Colonialism and Struggles for Independence in Amitav Ghosh's The Shadow Lines (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present article turns round investigating the elements of postcolonialism in one of AmitavGhosh's novels The Shadow Lines. He has intertwined and examined the impacts of colonialism on theculture and society of two fundamental neighboring urban communities, to be specific Calcutta andDhaka. Presenting an exhaustive political and social change, the novel illuminates starting awareness ofthe social, psychological, and social inferiority authorized by colonizers, and presentations struggle ofsubaltern people for ethnic, social, and political independence. Throughout the novel the essayistexpressly and verifiably radiates starts or traces of postcolonial principles to show his enthusiasm fordepicting the fallout of colonization particularly in a time after the liberation.